BS EN 4165-015. Aerospace series. Connectors, electrical, rectangular, modular. Operating temperature 175 Â°C continuous. Part 015. Round chimney for accessory (1 per module cavity), 2 and 4 modules. Product standard (27th June 2023) - British Standards Institution,
No abstract available